Efektivitas Video Edukasi dalam Meningkatkan Pengetahuan dan Sikap Remaja Perempuan Mengenai Kesehatan Reproduksi di SMAN 1 Kayuagung Tahun 2019 - Poppy Theolisita Tarigan; Amrina Rosyada (HB PRESS, 2021)
Transition from childhood to adulthood requires individuals to experience rapid changes in all aspects of their lives, which often makes the individual or adolescent in conflict with himself or the social environment. Knowledge and good attitude related to reproductive health will help adolescents in preparing adulthood. This quasi-experimental study used a pretest-posttest with control group design using educational videos as the intervention and simple counseling as the control. A total of 21 respondents were in the control group and 21 respondents were in the intervention group. The results showed that the intervention media in the form of educational videos were effective in improving students' attitudes compared to simple extension media with a significant p-value of 0,002. Educational videos and simple counseling were equally effective in improving student knowledge related to reproductive health as seen from the significant p-value of the independent t-test (0,131).